(untitled) (CIPEEX, 2025)
The dissemination of false news during electoral periods has become a significant challenge for contemporary democracies, especially in light of the popularization of social media. In Brazil, the impact of disinformation on the electoral process has generated debates about the boundaries between freedom of expression and the role of the State in combating this phenomenon. This study aims to analyze the conflicts between the protection of freedom of expression and the measures adopted to confront disinformation within the scope of Brazilian Electoral Law. It seeks to understand how the legal system has dealt with this tension. A qualitative methodology was employed, based on bibliographic review, legislative analysis, and examination of decisions of the Superior Electoral Court (TSE), particularly since the 2018 elections, when disinformation began to play a more evident role in the political arena. The results indicate that the Judiciary has adopted a more active stance in combating disinformation, which has generated criticism regarding possible excesses and risks to freedom of expression. Nevertheless, there is an effort to establish legal parameters to ensure the integrity of the electoral process without compromising fundamental rights. It is concluded that confronting disinformation must be based on clear and proportional legal criteria, ensuring that any limitations on freedom of expression do not turn into censorship but rather serve as legitimate instruments for the protection of democracy.